COPULA BERSYARAT UNTUK MENGESTIMASI VALUE at RISK (Studi Kasus Saham Nasdaq dan S&P500) - , MELVINA OCHTORA DAMANIK ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Value at Risk (VaR) plays a central role in risk management nowadays. There are several methods that can be used to estimate VaR such as the Variance- Covariance, historical simulation and etc. Generally, these methods assume the normal distribution for the stock returns and the dependence between the stocks of portfolio estimated by linear correlation. In finance the normality is rarely an adequate assumptions and the linear correlation can not detect the the non linear dependence so the estimated VaR is not accurate. The concept of Copula is a very powerful tool for modeling joint distribution for any marginal distribution. Dependency measurement that used too is based on copula namely tail dependency. This minithesis studies about the concept of Copula and its application to estimates Value at Risk of a portfolio that composed by two stock indices ( Nasdaq and S&P500 period 13 August 2012 to 10 March 2014) which is each returns modeled by ARMA-GARCH obtain the residuals furthermore that used to model the Copula and estimate VaR.